Draft Proposals for Fifth Five Year Plan 1974-79 Andaman and Nicobar Islands - Planning Commission (Planning Commission, 1974)
The Ministry of Rehabilitation has been made responsible for the development of such "Special Areas" as may be indicated by the Prime Minister. the "Special Areas" referred to are those areas of the country where due to climatic, geographical or other reasons, economic and social development have been retarded and which are sparsely populated but may be richly endowed with natural resources.
Department of Rehabilitation Ministry of Labour and Rehabilitation, Andaman and Nicobar Islands